FRI0645 Anti-drug antibodies to certolizumab pegol are associated with low drug levels and reduced clinical response at 3 months in patients with inflammatory joint diseases. data from the nor-dmard study. (12th June 2018) - Gehin, J. E.; Goll, G. L.; Warren, D. J.; Syversen, S. W.; Sexton, J.; Strand, E. K.; Kvien, T. K.; Bolstad, N.; Lie, E.
Abstract : Background: Anti-drug antibodies (ADAb) to biological drugs predispose patients to low drug levels and lack of treatment response. For certolizumab pegol (CP) knowledge about the frequency and clinical relevance of ADAb is limited in patients with inflammatory joint diseases (IJD). Objectives: To assess the frequency and clinical relevance of early ADAb development in patients with inflammatory joint diseases treated with CP. Methods: Patients from the NOR-DMARD study (n=310) with a clinical diagnosis of rheumatoid arthritis (RA, n=91), psoriatic arthritis (PsA, n=61), axial spondyloarthritis (axSpA, n=116) and other IJD (42) starting treatment with CP, who had available biobank sample at 3 months follow-up, were included. Serum samples are non-trough samples collected at 3 months. Drug concentrations were analysed using an in-house immunofluorometric assay automated on the AutoDELFIA immunoassay platform. ADAb was detected by a principal assay measuring neutralising ADAb and two confirmational tests (antigen-bridging test and a 3-step immunofluorometric assay). Patients with RA, PsA and axSpA were included in response analyses. Treatment response was defined by EULAR good/moderate response in RA, DAS28 improvement ≥0.6 in PsA, and ASDAS clinically important improvement (CII) in axSpA. Results: After 3 months of treatment, 19 of 310 (6.1%) patients were ADAb positive (5 RA, 4 PsA, 6 axSpA and 4 other IJD). ADAb positive patients had significantly lower CP levels than ADAb negative patients, median 1.0 (IQR 0.2–6.8) vs 34.4 (IQR 21.2–44.7) mg/L (P<0.001). Response data were available for 245 patients. Of these, only 1/11 (9%) ADAb-positive patients was classified as a responder, while 10/11 (91%) were non-responders. Among ADAb-negative patients with response data, 129/234 (55%) were responders, while 105/234 (45%) were non-responders. Conclusions: ADAb against CP were detected in 6.1% of patients after 3 months of treatment and were associated with low drug levels and reduced treatment response. These results suggest that drug levels and ADAb may be important for monitoring efficacy of treatment with TNF inhibitors, but the clinical significance needs to be examined in randomised clinical strategy trials. Disclosure of Interest: J. E. Gehin Consultant for: Roche, G. Goll Consultant for: Abbvie, Biogen, Boehringer Ingelheim, Orion Pharma, Eli Lilly, Novartis, Pfizer, MSD, Roche, UCB, D. Warren: None declared, S. Syversen Consultant for: Roche, J. Sexton: None declared, E. Strand Consultant for: Pfizer, T. Kvien Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Epirus, Hospira, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz, UCB, N. Bolstad Consultant for: Pfizer, Orion Pharma, Napp pharmaceuticals, Takeda, Roche, E. Lie: None declared